Electric-Field Induced Tricritical Points in Antiferroelectric Liquid Crystal - Fajar, Andika (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2010)
The electric field effect on the smectic-A - smectic-C* phase transition of antiferroelectric liquid crystal have been investigated theoretically. A phenomenological theory under DC field has been developed to establish the calculated hysteresis loop and the E (electric field)âˆ’T (temperature)phase diagram, in which a tricritical point was found.